Family poverty and neighborhood poverty: Links with children's school readiness before and after the Great Recession. (August 2017) - Wolf, Sharon; Magnuson, Katherine A.; Kimbro, Rachel T.
Abstract: This paper examines how neighborhood and family poverty predict children's academic skills and classroom behavior at school entry, and whether associations have changed over a period of twelve years spanning the Great Recession. Utilizing the Early Childhood Longitudinal Study–Kindergarten 1998 and 2010 cohorts and combined with data from the U.S. Census and American Community Survey, we find that the proportion of kindergarten children living in moderate and high poverty neighborhoods increased from 1998 to 2010, and that these increases were most pronounced for non-poor and white children. Using OLS and fixed effects regression analyses and holding family poverty constant, we find that children in neighborhoods with higher levels of poverty start school less ready to learn than their peers. Specifically, children from the highest poverty neighborhoods start school almost a year behind children from the lowest poverty neighborhoods in terms of their academic skills. In addition, we find that the academic skills gap between poor- and non-poor children within neighborhood poverty categories grew from 1998 to 2010, particularly in high poverty neighborhoods. These findings appear to be explained both by changes in the composition of families within neighborhood poverty categories and income increases among non-poor families. The findings indicate that neighborhood poverty may be a useful proxy to identify children and families in need of additional support. Highlights: The percent of kindergarteners in high poverty neighborhoods grew from 1998 to 2010. Increases were most pronounced for non-poor and white children. Children in high poverty neighborhoods are less school ready than their peers. The family poverty academic skills gap in higher poverty neighborhoods also grew. Neighborhood poverty may be a useful proxy to identify children in need of support.